Effects of Carbon Pricing on Inflation - Richhild Moessner (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study how carbon pricing has affected inflation ex-post, using dynamic panel estimation of New-Keynesian Phillips curves for 35 OECD economies from 1995 to 2020. As carbon pricing we consider prices of emissions trading systems (ETS) and carbon taxes. We find that an increase in prices of ETS by 10 per ton of CO2 equivalents increases energy CPI inflation by 0.8 percentage points (pp), and headline inflation by 0.08pp, but has no significant effects on food and core CPI inflation. We also find that an increase in carbon taxes by 10 per ton of CO2 equivalents increases food CPI inflation by 0.1pp, but has no significant effects on energy CPI inflation, headline and core CPI inflation.
Keywords: E31; E52; E58; Q48; Q58; 330; climate policies; carbon tax; carbon emission trading system; climate change; inflation